Managerial myopia and the mortgage meltdown - Kolasinski, Adam C.; Yang, Nan (Journal of Financial Economics, 2018)
Prominent policy makers assert that managerial short-termism was at the root of the subprime crisis of 2007–2009. Prior scholarly research, however, largely rejects this assertion. Using a more comprehensive measure of Chief Executive Officer (CEO) incentives for short-termism, we uncover evidence that short-termism indeed played a role. Firms whose CEOs were contractually allowed to sell or exercise more of their stock and options holdings sooner had more subprime exposure, a higher probability of financial distress, and lower risk-adjusted stock returns during the crisis, as well as higher fines and settlements for subprime-related fraud.